Pemasaran Dan Simulasi Kelayakan Kredit KPR Berbasis Web Pada KPR Sion Beach Residence - Pusvita, Ester Ayuk; Tandilo, Erna (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
The need for decent and affordable housing in Indonesia, particularly in Papua, continues to increase along with rapid population growth and urbanization. However, property marketing in this region still relies heavily on conventional methods such as printed brochures and face-to-face communication, which limits the effectiveness of information distribution and slows down the sales process. This research develops a web-based information system that integrates three main features: a house catalog, a mortgage simulation, and a reservation service. This system is designed using a systematic waterfall method, starting from needs analysis, system design with UML modeling, implementation using PHP and MySQL, and testing with black-box testing. The catalog feature displays a complete list of houses with specifications and prices, while the mortgage simulation feature allows users to calculate estimated installments based on the house price, tenor, and interest rate interactively and in real-time. The reservation service makes it easier for prospective buyers to book units online without having to visit the location in person. Test results show that all features run according to specifications and are easy to use by users. This system not only improves ease of access to information and transparency for prospective buyers, but also helps property developers expand their marketing reach, reduce conventional promotion costs, and accelerate the process of converting prospective buyers into active buyers. This research makes a significant contribution to the literature on digital transformation in the property sector, particularly in Papua, where technological innovation is still minimal. It also encourages increased access to housing finance in a more efficient and practical manner.